Al-MunÄfarah's skills and it impact on the development of Arabic rhetorical thought - Ayman Khamis Abdullatif Abu Mustaffa (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
This study is concerned with standing on the bragging about our Arab heritage, an attempt to elucidate the impact of this art on the development of Arab rhetorical thought, as the brags can be an early start for the pilgrims' theory that came as the result of the effects of modern stylistic studies. The study tries to root and clarify this through heritage books, and this is not what makes us stand as the defender of heritage, but rather it is an attempt to link the old with the modern, as ancient Arab literature was not separate from life, but rather discussed life issues in a literary manner. Also, in this type of art, we notice the availability of dramatic elements that can be indicative of theatrical art for Arabs, so bragging is not just a speech, but rather a recitation, movement and interaction with the audience.ØªÙ‡ØªÙ… Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¨Ø§Ù„ÙˆÙ‚ÙˆÙ Ø¹Ù„Ù‰ Ø§Ù„Ù…ÙØ§Ø®Ø±Ø© ÙÙŠ ØªØ±Ø§Ø«Ù†Ø§ Ø§Ù„Ø¹Ø±Ø¨ÙŠØŒ Ù…ØØ§ÙˆÙ„Ø© Ø§Ø³ØªØ¬Ù„Ø§Ø¡ Ø£Ø«Ø± Ù‡Ø°Ø§ Ø§Ù„ÙÙ† ÙÙŠ ØªØ·ÙˆØ± Ø§Ù„ØªÙÙƒÙŠØ± Ø§Ù„Ø¨Ù„Ø§ØºÙŠ Ø§Ù„Ø¹Ø±Ø¨ÙŠØŒ ÙØ§Ù„Ù…ÙØ§Ø®Ø±Ø§Øª ÙŠÙ…ÙƒÙ† Ø£Ù† ØªÙƒÙˆÙ† Ø¨Ø¯Ø§ÙŠØ© Ù…Ø¨ÙƒØ±Ø© Ù„Ù†Ø¸Ø±ÙŠØ© Ø§Ù„ØØ¬Ø§Ø¬ Ø§Ù„ØªÙŠ Ø¬Ø§Ø¡Øª Ø£Ø«Ø±Ø§ Ù…Ù† Ø¢Ø«Ø§Ø± Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø£Ø³Ù„ÙˆØ¨ÙŠØ© Ø§Ù„ØØ¯ÙŠØ«Ø©. ÙˆØ§Ù„Ø¯Ø±Ø§Ø³Ø© ØªØØ§ÙˆÙ„ ØªØ£ØµÙŠÙ„ Ø°Ù„Ùƒ ÙˆØªÙˆØ¶ÙŠØÙ‡ Ù…Ù† Ø®Ù„Ø§Ù„ ÙƒØªØ¨ Ø§Ù„ØªØ±Ø§Ø«ØŒ ÙˆÙ„ÙŠØ³ ÙÙŠ Ø°Ù„Ùƒ Ù…Ø§ ÙŠØ¬Ø¹Ù„Ù†Ø§ Ù†Ù‚Ù Ù…ÙˆÙ‚Ù Ø§Ù„Ù…Ø¯Ø§ÙØ¹ Ø¹Ù† Ø§Ù„ØªØ±Ø§Ø«ØŒ ÙˆÙ„ÙƒÙ† Ù‡ÙŠ Ù…ØØ§ÙˆÙ„Ø© Ù„Ù„Ø±Ø¨Ø· Ø¨ÙŠÙ† Ø§Ù„Ù‚Ø¯ÙŠÙ… ÙˆØ§Ù„ØØ¯ÙŠØ«ØŒ ÙØ§Ù„Ø£Ø¯Ø¨ Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø§Ù„Ù‚Ø¯ÙŠÙ… Ù„Ù… ÙŠÙƒÙ† Ù…Ù†ÙØµÙ„Ø§ Ø¹Ù† Ø§Ù„ØÙŠØ§Ø©ØŒ Ø¨Ù„ ÙƒØ§Ù† ÙŠÙ†Ø§Ù‚Ø´ Ù‚Ø¶Ø§ÙŠØ§ Ø§Ù„ØÙŠØ§Ø© Ø¨Ø£Ø³Ù„ÙˆØ¨ Ø£Ø¯Ø¨ÙŠ. ÙƒÙ…Ø§ Ø£Ù†Ù†Ø§ ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„ÙÙ† Ù†Ù„ØØ¸ ØªÙˆØ§ÙØ± Ø§Ù„Ø¹Ù†Ø§ØµØ± Ø§Ù„Ø¯Ø±Ø§Ù…ÙŠØ© Ø§Ù„ØªÙŠ ÙŠÙ…ÙƒÙ† Ø£Ù† ØªÙƒÙˆÙ† Ù…Ø¤Ø´Ø±Ø§ Ù„Ù„ÙÙ† Ø§Ù„Ù…Ø³Ø±ØÙŠ Ø¹Ù†Ø¯ Ø§Ù„Ø¹Ø±Ø¨ØŒ ÙÙ„ÙŠØ³Øª Ø§Ù„Ù…ÙØ§Ø®Ø±Ø© Ù…Ø¬Ø±Ø¯ Ø®Ø·Ø§Ø¨ØŒ Ø¨Ù„ Ù‡ÙŠ Ø¥Ù„Ù‚Ø§Ø¡ ÙˆØØ±ÙƒØ© ÙˆØªÙØ§Ø¹Ù„ Ù…Ø¹ Ø§Ù„Ø¬Ù…Ù‡ÙˆØ±.